Characterization and origin of late Devonian illitic clay deposits southwestern Iran - H.M.Baioumy, M.H.M.Gharaie, . (2007)
Illitic clay deposits of Esteghlal Mine that represent the largest refractory clay deposit in Iran were subjected to petrographical, mineralogical and geochemical investigations to examine their origin. Geological investigation showed that the illitic clay deposits of Esteghlal Mine intercalated with limestone beds rich in marine conodonts range in age from early to middle Famennian indicating the deposition of these illite deposits in marine environment during the early to middle Famennian. The deposits are composed mainly of illite with traces of kaolinite. Non-clay minerals are mainly very fine quartz and altered feldspars phenocrysts disseminated the very fine illite matrix